Formulaic theme and wisdom in Eddic poetry - Mawford, Christopher (2025)
This thesis explores how wisdom was delivered in Eddic poetry via the mechanism of formulaic theme. It demonstrates how the delivery of wisdom was a vital part of Eddic poetry, and that even poems not typically counted amongst the wisdom canon contain the same elements found in texts such as Hávamál. Additionally, this thesis explores how the formulaic delivery of wisdom developed from the earliest poems to the latest. This can further inform us on the fundamental creation of Eddic poetry. After establishing the methodology of this study in the introductory chapter, Chapter 2 provides an in-depth analysis of David Crowne’s 1960 theory of the ‘hero on the beach’ and how such a study may not just be translated from the Old English tradition to the Old Norse, but also across genres from the Heroic to Wisdom, using episodes from Hávamál to illustrate this. Following this study, the thesis progresses through the Codex Regius considering the following poems: Vafþrúðnismál, Grímnismál, Reginsmál, Fáfnismál, and Sigrdrífumál. Vafþrúðnismál and Grímnismál are found in Chapter 3, along with an analysis of the various forms of staging wisdom and the types of wisdom delivered. Chapter 4 features the three Sigurðr poems, and shows how the wisdom formulaic theme crosses over from the wisdom mythological poem in the heroic poetry, and the impact that this crossing over has on the delivery of wisdom. Chapters 5 and 6 are each dedicated to a single poem, Grípisspá and Sólarljóð respectively, as these poems serve to illustrate the different ways in which the theme developed and stagnated. Chapter 7 is the final summation chapter and shapes all the previous analysis into a cohesive theory of what precisely was needed in the theme, and what could change as its users needed. Finally, the conclusion offers some final commentary, before exploring how the theory could be studied further beyond the scope of this thesis.